PERAN PEMUDA KARANG TARUNA DALAM MENINGKATKAN KEPEDULIAN SOSIAL MASYARAKAT DESA TAJUNGAN - Romadhona, Salzabila; sahid, M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the role of youth of Karang Taruna in increasing the social awareness of the community in Tajungan Village, Kamal District, Bangkalan Regency. The background of this research rests on the phenomenon of declining social concern among rural communities, as well as the dominance of individualistic lifestyles that began to infect youth. Karang Taruna as a youth organization plays an important role in shaping character and building social awareness in the community. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through interviews, observations, and documentation of Karang Taruna administrators, community leaders, and local residents. The results of the study show that the Tajungan Village Youth Organization has carried out various programs such as social service, environmental cleanliness activities, and informal education that have a positive impact on the growth of social concern of the community. The main supporting factors in this success are the spirit of collectivity, the support of the village government, and the awareness of the youth themselves. Meanwhile, the obstacles faced include a lack of facilities, uneven community participation, and limited budgets. The conclusion of this study is that Karang Taruna has a strategic role in building a caring and empowered village community.